The Molecular Basis and Therapeutic Aspects of Cisplatin Resistance in Oral Squamous Cell Carcinoma - Cheng, Yali; Li, Shaoming; Gao, Ling; Zhi, Keqian; Ren, Wenhao (Frontiers in Oncology, 2021)
Oral squamous cell carcinoma (OSCC) is a kind of malignant tumors with low survival rate and prone to have early metastasis and recurrence. Cisplatin is an alkylating agent which induces DNA damage through the formation of cisplatin-DNA adducts, leading to cell cycle arrest and apoptosis. In the management of advanced OSCC, cisplatin-based chemotherapy or chemoradiotherapy has been considered as the first-line treatment. Unfortunately, only a portion of OSCC patients can benefit from cisplatin treatment, both inherent resistance and acquired resistance greatly limit the efficacy of cisplatin and even cause treatment failure. Therefore, it is urgent to elucidate the underlying mechanisms of cisplatin resistance in OSCC. Herein, this study outline the mechanisms of cisplatin resistance from the aspects of DNA damage and repair, epigenetic regulation, transport processes, programmed cell death and tumor microenvironment. In addition, this study summarize the strategies applicable to overcome cisplatin resistance, which can provide new ideas to improve the clinical therapeutic outcome of OSCC.